TCP PERFORMANCE ON LTE MOBILE NETWORK BY USING NS-3 - SAAD, AMNA; Suhaimi, Amira Syahmina (Journal of Computing Technologies and Creative Content, 2019)
Our inspiration for this research is to propose additional information to researchers based on our field of study: Networking systems. The world has been entering a new era of Long Term Evolution, LTE. There is different research gap in view based on internet connectivity, security, data privacy, system efficiency, data accuracy and another research gap that can be explored and research. The LTE supported mixed data, voice, video and messaging traffic and can provide new business opportunity based on LTE. In LTE cellular network, one of the most critical issues considered by researchers is to improve QoS (Quality of Service). Performances of protocols depend on network throughput, an end to end delay and packet drop. Performance analysis of improved protocols can be tested using simulation tools. The characteristic of LTE has been researched but it is in generic, makes it hard for any IT company to fulfill the characteristic. Our aim of the study is to provide information regarding the performance of LTE to LTE users, companies IT managers and LTE service providers.